2012
DOI: 10.5251/ajfn.2012.2.1.14.20
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin a and iron deficiency in pregnant women, lactating mothers and their infants in Adamawa State, Nigeria: a prospective cohort study

Abstract: We determined the breast-feeding patterns, Vitamin A and Iron supplement intake between various age groups of pregnant women in Adamawa state, Nigeria. Of the 161 pregnant women screened for this study, 73% were from Njoboliyo (NJ) (n=118) while 27% from GD Chanrai Memorial hospital (CMH) (n=43). Of the 161 women from the two study sites, women within the 15-24 age brackets had the highest number of study participants (65) 40%. Two-thirds of the study participants take supplements of Iron and Vitamin A (68%) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…When the diet of pregnant women is supplemented by these two haematinics the increase in red cell mass is doubled. 3 The practice of haematinic supplementation during pregnancy is widespread despite the fact that it is recommended only when iron deficiency is documented. 4 A recent study has cast considerable doubt on the assumption that it is appropriate to treat all pregnant women with iron and folic acid supplements, it also showed that the best feotal outcomes as indicated by small proportions of low birthweight infants and of preterm infants were achieved when haemoglobin (Hb) levels fell to <10.5 g/dl at some stage during gestation.…”
Section: Introductionmentioning
confidence: 99%
“…When the diet of pregnant women is supplemented by these two haematinics the increase in red cell mass is doubled. 3 The practice of haematinic supplementation during pregnancy is widespread despite the fact that it is recommended only when iron deficiency is documented. 4 A recent study has cast considerable doubt on the assumption that it is appropriate to treat all pregnant women with iron and folic acid supplements, it also showed that the best feotal outcomes as indicated by small proportions of low birthweight infants and of preterm infants were achieved when haemoglobin (Hb) levels fell to <10.5 g/dl at some stage during gestation.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding mature milk in the current contribution, the mean concentration of α-tocopherol and retinol for both groups of women (with a normal pregnancy and high-risk pregnancy) is very similar to most reports on these micronutrients. However, for women who, herein, had a high-risk pregnancy, the median concentration of α-tocopherol was higher than that detected in Polish women [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ] and in a group of adolescent mothers in Brazil [ 44 ]. In another study by Tokusoglu et al [ 45 ], the concentration of α-tocopherol in the mature milk of Turkish women was similar to that commonly observed in colostrum.…”
Section: Discussionmentioning
confidence: 72%
“…Iron is an important metal for all living things. In the human body iron is a major component of haemoglobin, which is the protein molecule in red blood cells that carries oxygen from the lungs to the tissues [7]. Iron is also an important component of various enzyme systems, such as the cytochromes, which are involved in oxidative metabolism [3].…”
Section: Introductionmentioning
confidence: 99%